Study of the remarkable reactivity of HNCO/urea with NO2 in the NOx SCR by urea process over an oxide-based catalyst. Issue 22 (20th October 2017) - Seneque, M.; Can, F.; Barreau, M.; Duprez, D.; Courtois, X.
Abstract : An exceptional reactivity between NO2 and the reductant species was demonstrated during NO2 -SCR experiments with urea, when only NO2 was used as NO x . Abstract : An exceptional reactivity between NO2 and probably HNCO was demonstrated over an oxide-based catalyst during NO2 -SCR experiments with urea as the injected reductant. This was observed when only NO2 was used as NO x, but not with gaseous NH3 as the reductant. Roughly, one third of the injected reductant reacted with NO2 and two thirds appeared to be oxidized by O2, the main product being N2 . 28 reactions may be involved in the observed results. A cooperative effect of NO2 with O2 was demonstrated and the observed global stoichiometry did not depend on the NO2 concentration for (NO2 /eq. NH3 )inlet ratio ≤1.